Effects of Hypothermia on Renal Functions for Patients undergo Coronary Artery Bypass Graft Surgery - Sabri, Khalid; hassan, Hakema (Iraqi National Journal of Nursing Specialties, 2012)
Objective: To determine the effectiveness of hypothermia on renal functions for patients undergoingcoronary artery bypass graft CABG surgery.Methodology: A purposive (non-probability) sample of (50) patients undergoing Isolated coronary arterybypass graft surgery consecutively admitted to the surgical ward, and they were followed up in theintraoperative, Intensive Care Unit (ICU) and in the postoperative (surgical ward). Post-operative renal functiontest (glumeruler filteration rate (GFR) by using the Crockroft-Gault formula and serum creatinine level) wasdetermined first week post operative and post operative renal function was classified on the base of peak ofthe serum creatinine level and decline of glomeruler filteration rate(GFR) as following : normal renal functionserum creatinine concentration and decline in(GFR) less than 25% from preoperative, moderate renaldysfunction increase serum creatinine concentration and decline in(GFR) 25%-50% from preoperative, severrenal dysfunction increase serum creatinine concentration and decline in(GFR) more than 50% frompreoperative test.Results: results of this study show that (78%) from the sample develop post operative renal dysfunction andthe highly percentage of them are male (50%), advance age 60-70 (60%), smoking (47.0%), diabetes mellitusDM (68%), cardiopulmonary bypass 180 and more (57.20%), New York Heart Association calcification NYHAclass III(47.5%) and patient without Intra Aortic Balloon Pump IABP(50,0%) . We conclude from the study thathighly percentage of patient undergoing isolated CABG may develop postoperative renal dysfunction evenwhen using hypothermic strategy as a protective measure and the patients with DM, male, advance age,smoker, prolong time of CPB (more than 180 minutes), NYHA class III and patient without IABP are consideredas patient at high risk to develop postoperative renal dysfunction.Recommendations: The researcher recommended that to find addition strategy rather than hypothermiato protect renal function especially with the high risk patients during isolated CABG surgery.